Influence of Performance Appraisal in Determining Academic Staff Performance in Public Universities in Uganda - Rwothumio, Joseph; Okaka, Wilson; Kambaza, Stephen; Kyomukama, Eugene (East African Nature and Science Organization, 2021)
In an effort by public universities to improve the performance of lecturers in Uganda, universities are implementing annual performance appraisal. Despite this move, ineffective teaching, low research and publication continue to prevail, making it difficult for public universities to produce the needed human resources for national development. This study investigated the relationship between performance appraisal and teaching and research outputs of academic staff in selected public universities. A mixed method design using convergent parallel approach was employed to collect and analyse data from a population of 4 Vice-Chancellors, 4 Directors of Human Resources and 1127 full-time academic staff. Four universities were selected using purposive sampling based on the year of establishment before 2011. The academic staff was selected by the use of the stratified random sampling technique. A total sample of 299 participants was involved made up of 291 academic staff, 4 directors of human resources and 4 Vice-chancellors in the study. Data collection employed the use of semi-structured questionnaires for the academic staff and interview guides for the Vice-Chancellors and Directors of Human Resources. Analysis of quantitative data collected was done using Pearson’s Correlation, linear regression and factor analysis. Qualitative data was analysed based on thematic content analysis. Results indicated that a moderate positive relationship existed between performance appraisal and academic staff teaching output in public universities (r = 0.452, p < 0.01) and a moderately positive relationship existed between performance appraisal and academic staff research output (r = 0.379, p < 0.01). It was recommended that Ugandan public universities need to revise the existing performance appraisal system to make it more relevant to the key work roles of academic staff of teaching and research outputs.